A first-in-man phase 1 trial for long-acting TransCon Growth Hormone. (April 2018) - Gilfoyle, David; Mortensen, Eva; Christoffersen, Eva Dam; Leff, Jonathan A.; Beckert, Michael
Abstract: TransCon growth hormone (GH) is a sustained-release inactive prodrug consisting of unmodified GH transiently bound to an inert carrier molecule designed to release fully active GH over a one-week period. This was a first-in-man phase 1 randomized trial was to evaluate the safety, tolerability, immunogenicity, pharmacokinetics (PK), and pharmacodynamics (PD) of a single dose of TransCon GH as compared to equivalent doses of daily GH (Omnitrope) or placebo in healthy adults. Forty-four healthy male adults were randomized to 4 cohorts of 11 subjects, distributed in a 7:2:2 ratio (TransCon GH: Omnitrope: placebo). A single injection of 4 possible TransCon GH doses (i.e., 0.04, 0.08, 0.16, or 0.24 mg GH/kg/wk) or two different Omnitrope doses (i.e., 0.08 or 0.16 mg GH/kg/wk divided into 7 equal daily doses) were administered with subjects evaluated for adverse events, immunogenicity, and GH and insulin-like growth factor-1 (IGF-1) levels. TransCon GH was well tolerated; no serious adverse events occurred, no injection site reaction differences between TransCon GH, Omnitrope, or placebo were identified, no nodules or lipoatrophy were reported, and no anti-GH binding antibodies or ECG changes were detected. Overall, the exposure of GH (Cmax ) and IGF-1 (AUC0–168 h ) following administration of equivalent doses of TransCon GH and Omnitrope were similar. GH and IGF-1 kinetics showed a dose-proportional increase following a single SC administration of TransCon GH and indicated that the prodrug is suitable for weekly administration. These results support advancement of TransCon GH to pediatric and adult GHD trials. Clinical trial registration numbers:NCT01010425 (clinicaltrials.gov ).